COUNSELLING FOR MITIGATING THE PSYCHO-SOCIAL TRAUMA OF FLOOD DISASTER VICTIMS - Undiyaundeye, Florence A; Denga, Daniel I (PEOPLE: International Journal of Social Sciences, 2018)
Psycho-social trauma comes about when a traumatic event overloads an individual’s capacity to cope with his or her usual emotional state. Psycho-social trauma cannot be predicted based on the events that precede them. Flood is an environmental hazard that occurs naturally and relatively sudden as a result of climate change. It happens in a devastating way and are brought down in good numbers. The resultant effects are particularly damaging in terms of properties and other economic/income generation structures. The focus of this work is on the psychosocial wellbeing of the victims. There is an assumption that women are more likely to suffer disproportionately in most disasters more especially flood, thee is hence they are more vulnerable due to minimal access to source of emergency. The core concept here is to prevent stress disorder in the victims of flood and provide coping interventions for traumatized people from the aftermath of major flood disaster leading to displacement from homes and work place. Most flood victims make more emotional investment and are more likely to experience more post traumatic stress disorder associated with flood and consequently become more devastated emotionally and psycho-socially as it happens. The authors hold a strong view that if psycho-social therapy is applied to victims irrespective of standing, it will remove ugly memories of the disturbance; extinguish the fears associated with the stressful events especially that which relates to re-location and loss of victims’ property. The conclusion implies an integrative approach involving experts from diverse field of human being endeavours particularly counselors who are expected to mitigate victims’ state of depression, anxiety and other flood inducing.